2003
DOI: 10.4141/s02-038
|View full text |Cite
|
Sign up to set email alerts
|

The influence of understory vine maple on forest floor and mineral soil properties in coastal temperate forests

Abstract: Tashe, N. C. and Schmidt, M. G. 2003. The influence of understory vine maple on forest floor and mineral soil properties in coastal temperate forests. Can. J. Soil Sci. 83: [35][36][37][38][39][40][41][42][43][44]. In coastal forests of the Pacific Northwest, vine maple (Acer circinatum Pursh) is a common understory tree species. We studied the influence of vine maple, growing in the understory of a stand of Douglas-fir [Pseudotsuga menziesii (Mirb.) Franco] and western hemlock [Tsuga heterophylla (RAF.) Sarg.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 20 publications
3
14
1
Order By: Relevance
“…Greater N availability beneath bigleaf maple may be due to rapid rates of decomposition (Harmon et al 1990) and relatively high N concentrations of bigleaf maple litter (Valachovic et al 2004). The finding of potentially greater N availability beneath bigleaf maple in our study is similar to findings of previous researchers (Tashe and Schmidt 2003;Turk 2006).…”
Section: ; Turk 2006)supporting
confidence: 93%
See 1 more Smart Citation
“…Greater N availability beneath bigleaf maple may be due to rapid rates of decomposition (Harmon et al 1990) and relatively high N concentrations of bigleaf maple litter (Valachovic et al 2004). The finding of potentially greater N availability beneath bigleaf maple in our study is similar to findings of previous researchers (Tashe and Schmidt 2003;Turk 2006).…”
Section: ; Turk 2006)supporting
confidence: 93%
“…Differences in litter inputs between broadleaves and conifers can lead to differences in forest floor properties and possibly nutrient availability. Many studies comparing the influence of broadleaves and conifers on soil properties have used an approach where soil properties were compared on plots beneath the canopies of broadleaves and conifers (Fried et al 1990;Ogden and Schmidt 1997;Tashe and Schmidt 2003;Turk 2006). These studies indicate whether a broadleaf species has an effect on properties of the soil, but they do not provide information about the spatial extent of that influence.…”
mentioning
confidence: 99%
“…One of the plots with No Litter treatment was excluded from the analyses because it is surrounded by vine maple (Acer circinatum Pursh), which has been shown to dramatically alter soil pH, C, and N content (Tashe and Schmidt 2003). We also found that respiration values from this plot were fundamentally different from other plots of this treatment.…”
Section: Statistical Analysis and Annual Summationmentioning
confidence: 96%
“…Ogden and Schmidt (1997) found that vine maple plots had significantly thinner forest floors than conifer plots. Tashe and Schmidt (2003) found vine maple plots to have significantly thicker Ah horizons than conifer plots, although no statistical differences were observed for the L, F or H horizons.…”
Section: Mineral Soil Propertiesmentioning
confidence: 57%
“…Krajina et al (1982) suggested Mulls are typical of bigleaf maple litter. Tashe and Schmidt (2003) observed Mulls beneath vine maple and abundant Mors and Moders beneath conifer plots. Occasionally Mors were also observed under vine maple (Tashe and Schmidt, 2003).…”
Section: Humus Form Classificationmentioning
confidence: 95%